Orbital decompression for thyroid-associated orbitopathy in England: trends over time and geographical variation. - Dharmasena, A; Keenan, T; Goldacre, M (2014)
AIMS: The aims of this study were to examine trends over time and geographical variation in the annual incidence of surgical orbital decompression for thyroid-associated ophthalmopathy (TAO) in England. METHODS: Data on hospital admissions for orbital decompression surgery in patients with thyroid disease were analysed using English national Hospital Episode Statistics for admissions from 1991-2011. RESULTS: Annual rates of orbital decompression surgery performed for patients with thyroid disease increased from 0.06 (95% confidence interval, 0.04--0.09) per 100,000 population in 1991, to 0.62 (0.54--0.67) in 2008, and then fell to 0.56 (0.48--0.60) in 2011. The surgical rate was highest in women aged 45--64 years. Geographical analysis showed significant variation across strategic health authority areas in surgical rates, from 0.22 (0.14-0.35) to 1.04 (0.79-1.34) people per 100,000 population per year in 2007-2011. CONCLUSION: The incidence of orbital decompression surgery performed annually in England has increased substantially over the past two decades, but peaked in 2008 and decreased since then. Significant geographical variation exists in surgical rates. Potential reasons for the decline include improved management of thyroid disease itself, but altered threshold in medical versus surgical management of TAO may also have played a role. The Amsterdam Declaration and EUGOGO treatment guidelines may also have influenced decisions about whether to operate on these patients.